Relationship of environmental factors in pond water and dynamic changes of gut microbes of sea bass Lateolabrax japonicus - Zhu, Zheng; Xu, Yu-Min; Liang, Jun-Han; Huang, Wei; Chen, Jin-Ding; Wu, Si-Ting; Huang, Xiao-Hong; Huang, You-Hua; Zhang, Xiao-Yang; Sun, Hong-Yan; Qin, Qi-Wei (Frontiers in Microbiology, 2023)
The effect of structure of gut microbes of organisms on the health of host has attract increasing attention. Sea bass Lateolabrax japonicus is an important farmed fish in China. Studying the dynamic changes of intestinal bacterial communities in L. japonicus, and the relationship between water environment and intestinal microorganisms are very important for healthy aquaculture. Here, the diversity and abundance of the gut microbial communities of L. japonicus were evaluated during the aquaculture using 16S rRNA Illumina sequencing. Both the opportunistic pathogens (Aeromonas,1.68%; Vibrio, 1.59%; and Acinetobacter, 1.22%) and the potential probiotics (Lactobacillus, 2.27%; Bacillus, 1.16%; and Lactococcus, 0.37%) were distributed in the L. japonicus gut. The increasing concentration of nitrogen of water environments with the increase of aquaculture time significantly correlated with shifts in the microbial community structure: 40.04% of gut microbial changes due to nitrogen. Higher concentrations of nitrogen showed a significantly negative correlation with intestinal probiotics in L. japonicus. The results indicate that the abundance of intestinal bacteria of L. japonicus is mainly driven by the changes of environmental factors (e.g., nitrogen), and it's very important that the linking environmental parameters with bacterial data of guts used as an early warning indicator in L. japonicus heath aquaculture.